2000
DOI: 10.12693/aphyspola.97.25
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Transport and Thermal Properties of the Solid Solutions U1-xThxCu5M (M = Al, Ga, In and Sn)

Abstract: UCu5M-type compounds are moderate heavy fermion systems with an antiferromagnetic order below TN = 18, 16-25, and 25 K for M = Al, (Ga, In), and In, respectively, and a ferrimagnetic order with TO = 54 K for M = Sn. We present the results of magnetoresistance measurements as a function of temperature and applied magnetic field for the pure compounds and for their solid solutions containing Th, i.e. U1-xΤhxCu5M. Only in the case of UCu5In a substantial positive contribution to the magnetoresistance was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The results of magnetoresistance measurements on the UCu 5 Al polycrystalline sample, have already been partly reported previously, e.g. taken either up to 8 T [48] or 13 T [49]. The temperature dependences of the electrical resistance R (arb.unit) at 0, 6, 10 and 13 T for UCu 5 Al are given in Fig.…”
Section: Ucu 5 Al [Tetragonal Own Type] and Ufe 5 Sn [Orthorhombic supporting
confidence: 67%
See 2 more Smart Citations
“…The results of magnetoresistance measurements on the UCu 5 Al polycrystalline sample, have already been partly reported previously, e.g. taken either up to 8 T [48] or 13 T [49]. The temperature dependences of the electrical resistance R (arb.unit) at 0, 6, 10 and 13 T for UCu 5 Al are given in Fig.…”
Section: Ucu 5 Al [Tetragonal Own Type] and Ufe 5 Sn [Orthorhombic supporting
confidence: 67%
“…All of them form a class of moderate heavy fermion compounds, with γ(0) around 100-400 mJ/mol K 2 which has recently been studied intensively in Wrocław on poly-and single-crystalline samples [48]. These compounds though display at low temperatures moderately enhanced γ(0)-values, at the same time exhibit magnetic order of the Kondo-reduced magnetic moments.…”
Section: Ucu 5 Al [Tetragonal Own Type] and Ufe 5 Sn [Orthorhombic mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Magnetic sus-ceptibility, NMR, specific heat, and electrical resistivity measurements 1,6,7 have revealed that antiferromagnetic ͑AF͒ order sets in below 18 K. The magnetic structure, determined by neutron powder diffraction scattering, is of a sinusoidally modulated type (k ជ ϭ0, 0, 0.55͒ with the amplitude of uranium moments ( ord ϭ1.45 B at 1.4 K͒, parallel to the c axis. 5 Interesting to recall that the Kondo-like behavior of the temperature-dependent electrical resistivity in conjunction with an enhancement of the C p /T ratio has classified UCu 5 Al as a medium heavy-fermion system.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the two lines 4f 5=2 and 4f 7=2 can be decomposed into a highly asymmetric main line and two symmetric satellites at 7.1 and 2.6 eV higher binding energies. The pronounced asymmetry of the main lines is considered to be caused by many-body e ects of the electron±hole interaction in the photoemission process (van Veenendaal et al 1993, Bocquet et al 1995. According to the Doniach±S Ï unjic (1970) theory, the asymmetry of the main line is due to the angular dependence of screening charges in the electron±hole interaction during the photoemission process and is described by a singularity parameter ¬.…”
mentioning
confidence: 99%